To the fauna (Insecta, Odonata)of Southern Kazakhstan (Eurasian Journal of Ecology, 2016)
On the territory of Southern Kazakhstan 33 species of Odonatawasdetected from mountains, steppes and deserts. The quite differences of species composition depending of inhabitants was shown.
Keywords: Odonata; fauna; South Kazakhstan